Strategi Komunikasi Politik Partai Gerindra Di Kota Palangka Raya Dalam Pemilu 2024 Dan Pilkada 2025 - Rahman , Abdul; Pransiska, Anita; R Siagian, Enika; Fernanda Fajeri, Mochammad; Salsabila; Sunarno, Ali; Karliani, Eli (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2025)
This study aims to examine the Gerindra Party's political communication strategy in conveying its political message to the people of Palangka Raya in the 2024 General Election and the 2025 Regional Election. Through interviews with party cadres, this study found that Gerindra's political communication in Palangka Raya relies heavily on two main aspects: the use of social media and direct meetings. Social media was chosen because of its efficiency in reaching a wider audience, especially young voters, while direct meetings were emphasized more to reach community groups in areas that are not yet fully accessible by the internet. The Gerindra Party also faces challenges in dealing with hoaxes and inaccurate information and adapting to differences in communication at the central and regional levels. These findings are expected to provide insight into political communication strategies in more effective campaigns in the future.